Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Terhadap Hasil Belajar IPA Terpadu Siswa Kelas VIII SMP Negeri 22 Merangin Tahun Pelajaran 2018/2019 - Astuti, Tutut Puji; Wulandari, Eko; Viza, Rivo Yulse (BIOCOLONY, 2018)
This research is motivated by result of integrated science learning student of classVII still have not reached the KKM that is 75. One of the learning models that canimprove student learning outcomes is to use the TPS type cooperative learningmodel. This study aims to find out and describe the Think Pair Share (TPS) type ofcooperative learning better than conventional models on integrated sciencelearning outcomes for grade VIIIstudent of SMP Negeri 22 Merangin in 2018/2019academic year. This type of research is experimental research, the research designis post test only control design. The population in this study were all eight gradestudent of SMP 22 Merangin in the 2018/2019 school year consisting of 2 classes.The sampling technique in this study is total sampling, and to determine theexperimental class and control class using simple random sampling. Datacollection technigues are test techniques, trought essay tests totaling 8 items. Dataanalysis techniques used to test hypotheses are t-test. The result of the study, in theexperimental class obtained an average value of 78,6, while in the control classobtained an average value of 75,05, then the data was analyzed using the t-test.Hypothesis test results are obtained, t-count=1,803 an t-table=1,689. Because tcount > t-table then Ho is rejected and Ha is accepted. So it can be concluded thatthe integrated science learning outcomes using cooperative learning model typeThink Pair Share (TPS) is better than using conventional learning model class VIIISMP Negeri 22 Merangin in the 2018/2019 school year.